An ethyl cellulose-based phase change organic gel, and a preparation method and application thereof

CN122978679APending Publication Date: 2026-10-27LUZHOU NORTH CELLULOSE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611146787.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,其仍存在热循环过程中网络结构易塌陷的问题

Benefits of technology

本发明基于乙基纤维素、疏水性二氧化硅及纤维素纳米晶三者之间所形成的氢键交联网络可为凝胶提供机械强度这一特性;利用乙基纤维素及纤维素纳米晶自身可降解的特性提升了复合凝胶的环保性能,从而构建了一种兼具良好机械性能且绿色环保的生物质基复合凝胶,以满足其在油污吸附领域中的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978679A_ABST
    Figure CN122978679A_ABST
Patent Text Reader

Abstract

The application discloses an ethyl cellulose-based phase change organic gel and a preparation method and application thereof, and belongs to the technical field of new materials. The ethyl cellulose-based phase change organic gel comprises the following components in percentage by weight: 60-70wt% of polyethylene glycol, 15-20wt% of ethyl cellulose, 12-15wt% of hydrophobic fumed silica and 3-5wt% of a strength enhancer. The application is based on the characteristic that a hydrogen bond cross-linking network formed among ethyl cellulose, hydrophobic fumed silica and the strength enhancer can provide mechanical strength for the gel; the environmental protection performance of the composite gel is improved by using the degradable characteristic of ethyl cellulose; the preparation process is simple, and complex equipment and high energy consumption are not needed; and the material has good heat storage performance, cycle performance and green environmental protection and the like, so that the material can be well applied to the thermal management field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new materials technology, specifically relating to an ethyl cellulose-based phase change organic gel, its preparation method, and its application. Background Technology

[0002] With the escalating global energy crisis and the increasing urgency of energy conservation and emission reduction, the imbalance between heat supply and demand caused by the intermittency of renewable energy, high building energy consumption, and difficulties in thermal management of electronic equipment is becoming increasingly prominent, posing a severe challenge to sustainable development and the ecological environment. Phase change materials, especially solid-liquid phase change materials, are considered a promising technology for achieving efficient heat storage and intelligent temperature control because they can absorb or release a large amount of latent heat during the phase change process while maintaining a near-constant temperature. However, commonly used solid-liquid phase change materials, such as polyethylene glycol, generally suffer from problems such as easy leakage in the molten state, poor shape stability, poor compatibility with the matrix, and performance degradation after long-term cycling. Therefore, developing a novel shaped phase change material that combines high phase change enthalpy retention, excellent shape stability, good thermal cycling performance, and environmental friendliness is of great practical significance and strategic value for promoting the practical application of phase change energy storage technology.

[0003] Organic gels, as viscoelastic soft solids formed by the self-assembly of polymers or low-molecular-weight gelling agents to create a three-dimensional network structure and bind a liquid oil phase within it, exhibit unique advantages in the encapsulation of phase change materials due to their high oil-binding capacity, tunable microstructure, and good compatibility. Theoretically, the three-dimensional network within organic gels can stably retain molten phase change materials within the network microregions through multiple mechanisms such as physical entanglement, capillary adsorption, and hydrogen bonding, achieving a transition from solid-liquid phase change to solid-solid (or solid-gel) phase change, thereby effectively preventing leakage. However, single-component organic gel systems, especially pure ethyl cellulose-based organic gels, suffer from inherent defects such as insufficient mechanical strength, poor long-term thermal cycling stability, and large phase change enthalpy loss, which greatly limit their practical application in phase change energy storage.

[0004] Ethyl cellulose, as an important derivative of cellulose, possesses outstanding advantages such as good biocompatibility, biodegradability, excellent film-forming properties, and high chemical stability. Organic gels prepared using ethyl cellulose as a matrix inherit the common advantages of organic gel materials (such as three-dimensional network binding capacity and high oil-binding capacity) while also exhibiting the green and environmentally friendly characteristics of bio-based materials, making them an ideal choice for next-generation high-efficiency shape-stabilized phase change materials. However, they still suffer from the problem of network structure collapse during thermal cycling. Furthermore, the preparation of existing ethyl cellulose-based phase change composites often involves complex chemical modifications or harsh process conditions. Therefore, developing a novel ethyl cellulose-based phase change organic gel with a simple preparation process and recyclability is of great practical significance for solving the increasingly serious problems of energy storage and thermal management. Summary of the Invention

[0005] To address the aforementioned shortcomings of existing technologies, the present invention aims to provide an ethyl cellulose-based phase change organic gel, its preparation method, and its application. This phase change organic gel has a simple preparation process, requires no complex equipment or high energy consumption, and possesses excellent heat storage performance, cycle performance, and environmental friendliness, making it well-suited for application in the field of thermal management.

[0006] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: an ethyl cellulose-based phase change organic gel is provided, comprising the following components by weight percentage: polyethylene glycol 60-70 wt%, ethyl cellulose 15-20 wt%, hydrophobic fumed silica 12-15 wt%, and strength enhancer 3-5 wt%.

[0007] The beneficial effects of this invention are as follows: the hydroxyl groups of ethyl cellulose and the hydroxyl / carboxyl groups on the surface of the strength enhancer can form a large number of intermolecular hydrogen bonds with the ether oxygen and hydroxyl groups of polyethylene glycol. At the same time, the silanol groups remaining on the surface of hydrophobic fumed silica can also participate in hydrogen bond association. The three together build a continuous and stable three-dimensional cross-linked network skeleton. This process does not require additional chemical cross-linking agents and relies entirely on non-covalent hydrogen bonding and molecular chain entanglement to complete physical cross-linking. This preserves the biodegradable properties of natural biomaterials such as ethyl cellulose and avoids the environmental burden caused by chemical cross-linking agent residues. Furthermore, the rigid structure of the strength enhancer provides support in the network, allowing the hydrogen bond cross-linked network to uniformly disperse external forces. This effectively compensates for the insufficient mechanical strength of the pure ethyl cellulose skeleton and the problem of network collapse during thermal cycling. At the same time, this dense and stable hydrogen bond network can firmly encapsulate the phase change component polyethylene glycol, inhibiting the leakage of the phase change medium during repeated thermal cycling and significantly reducing the phase change enthalpy loss. Ultimately, while endowing the material with excellent mechanical properties and green environmental protection characteristics, it significantly improves its long-term thermal cycling stability and meets the needs of the thermal management field.

[0008] Based on the above technical solution, the present invention can be further improved as follows: Furthermore, an ethyl cellulose-based phase change organic gel comprises the following components by weight percentage: 70 wt% polyethylene glycol, 15 wt% ethyl cellulose, 12 wt% hydrophobic fumed silica, and 3 wt% strength enhancer.

[0009] Furthermore, the strength enhancer is cellulose nanocrystals and / or carboxylated cellulose nanocrystals.

[0010] Furthermore, the polyethylene glycol is at least one of polyethylene glycol 1000, polyethylene glycol 2000, and polyethylene glycol 3400.

[0011] The preparation method of the above-mentioned ethyl cellulose-based phase change organic gel includes the following steps: Ethyl cellulose is dissolved in a solvent, hydrophobic fumed silica and a strength-enhancing agent are added, and the mixture is stirred until uniformly dispersed. Polyethylene glycol is then added, and stirring continues until uniformly dispersed. Finally, the resulting solution is dried to constant weight at room temperature and pressure. More specifically: Ethyl cellulose is dissolved in a solvent, hydrophobic fumed silica is added, and the mixture is stirred until uniformly dispersed. A strength-enhancing agent is then added, and stirring continues until uniformly dispersed. Polyethylene glycol is then added, and stirring continues until uniformly dispersed. The resulting solution is then placed in a mold and dried to constant weight at room temperature and pressure.

[0012] The beneficial effects of this invention are as follows: The preparation method of this invention is carried out at room temperature and pressure, which is different from freeze drying, which relies on solvent sublimation to avoid liquid surface tension, and also different from vacuum drying, which relies on negative pressure to accelerate solvent evaporation. In the stirring stage before drying, the components of this invention have formed a three-dimensional physical network skeleton with a certain structural rigidity through a large number of intermolecular hydrogen bonds. The capillary forces generated in the pores during solvent evaporation can be uniformly dispersed and canceled by the pre-built hydrogen bond cross-linking network, avoiding the serious shrinkage and cracking of the skeleton that easily occurs when pure ethyl cellulose gel is dried at room temperature and pressure. The multi-space network structure of the gel can be completely preserved without special drying conditions. Finally, an ethyl cellulose-based phase change organic gel with a complete structure and uniform pore distribution is obtained directly under room temperature and pressure, which greatly simplifies the preparation process and reduces the process cost.

[0013] Furthermore, the solvent is tert-butanol.

[0014] The application of the above-mentioned ethyl cellulose-based phase change organic gel in oil adsorption.

[0015] The components used in this invention, ethyl cellulose and polyethylene glycol, are both oleophilic and hydrophobic components. Therefore, the final material can be used for oil stain adsorption.

[0016] The application of the above-mentioned ethyl cellulose-based phase change organic gel in the preparation of thermally managed phase change materials.

[0017] The present invention has the following beneficial effects: This invention is based on the characteristic that the hydrogen bond cross-linking network formed between ethyl cellulose, hydrophobic silica, and cellulose nanocrystals can provide mechanical strength to the gel; by utilizing the biodegradable properties of ethyl cellulose and cellulose nanocrystals, the environmental performance of the composite gel is improved, thereby constructing a biomass-based composite gel that has both good mechanical properties and is environmentally friendly, so as to meet its application in the field of oil pollution adsorption.

[0018] The gel prepared by the one-step molding method of this invention can be in sheet form, and its material is superior to powder or granular materials. The heat storage performance of the ethyl cellulose-based phase change organic gel was tested, and the results showed that the phase change enthalpy of this material is as high as 130.5 J / g. This demonstrates the superiority of the phase change organic gel material of this invention and its great potential for application in the field of thermal management. Attached Figure Description

[0019] Figure 1 The infrared spectrum of the ethyl cellulose-based phase change organic gel obtained in Example 1 is shown. Detailed Implementation

[0020] The hydrophobic fumed silica used in this invention was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., BET: 300 m 2 / g.

[0021] The examples given below are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, conditions in the examples are performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0022] Example 1: An ethyl cellulose-based phase change organic gel comprises the following components in weight percentages: 100070wt% polyethylene glycol, 15wt% ethyl cellulose, 12wt% hydrophobic fumed silica, and 3wt% cellulose nanocrystals.

[0023] The preparation method of the above-mentioned ethyl cellulose-based phase change organic gel includes the following steps in sequence: (1) Dissolve 0.45g of ethyl cellulose (EC) in tert-butanol solvent by stirring and heating; (2) Add 0.36g of hydrophobic silica (SiO2) to the product obtained in step (1) and stir until it is evenly dispersed; (3) Add 0.09 g of cellulose nanocrystals (CNC) to the product obtained in step (2) and stir until uniformly dispersed; (4) Add 2.1g of polyethylene glycol 1000 (PEG) to the product obtained in step (3) and stir until evenly dispersed; (5) Place the solution obtained in step (4) into a mold and dry it to constant weight at room temperature and pressure to obtain ethyl cellulose-based phase change organic gel, denoted as PEG / EC-SiO2-CNC.

[0024] Example 2: An ethyl cellulose-based phase change organic gel comprises the following components in weight percentages: 60 wt% polyethylene glycol 1000, 20 wt% ethyl cellulose, 15 wt% hydrophobic fumed silica, and 5 wt% cellulose nanocrystals.

[0025] The preparation method of the above-mentioned ethyl cellulose-based phase change organic gel is the same as that in Example 1.

[0026] Example 3: An ethyl cellulose-based phase change organic gel comprises the following components in weight percentages: 100065wt% polyethylene glycol, 18wt% ethyl cellulose, 13wt% hydrophobic fumed silica, and 4wt% cellulose nanocrystals.

[0027] The preparation method of the above-mentioned ethyl cellulose-based phase change organic gel is the same as that in Example 1.

[0028] Example 4: Example 4 differs from Example 1 only in that cellulose nanocrystals are replaced with carboxylated cellulose nanocrystals; otherwise, they are the same as the examples.

[0029] Comparative Example 1: A phase change organic gel comprising the following components by weight percentage: polyethylene glycol 1000 70wt% and ethyl cellulose 30wt%.

[0030] The preparation method of the above-mentioned phase change organic gel includes the following steps: Ethyl cellulose was dissolved in tert-butanol solvent by stirring and heating, then polyethylene glycol 1000 was added and stirred until uniformly dispersed. The resulting solution was placed in a mold and dried to constant weight at room temperature and pressure to obtain the final product.

[0031] Comparative Example 2: A phase change organic gel comprising the following components by weight percentage: 1000 polyethylene glycol 70wt% and hydrophobic fumed silica 30wt%.

[0032] The preparation method of the above-mentioned phase change organic gel includes the following steps: Hydrophobic fumed silica was dispersed in tert-butanol solvent, then polyethylene glycol 1000 was added and stirred until uniformly dispersed. The resulting solution was placed in a mold and dried to constant weight at room temperature and pressure to obtain the final product.

[0033] Comparative Example 3: A phase change organic gel comprising the following components by weight percentage: 1000 polyethylene glycol 70wt%, ethyl cellulose 18wt%, and hydrophobic fumed silica 12wt%.

[0034] The preparation method of the above-mentioned phase change organic gel includes the following steps: Ethyl cellulose was dissolved in tert-butanol solvent by stirring and heating. Hydrophobic silica was added and stirred until uniformly dispersed. Then, polyethylene glycol 1000 was added and stirred until uniformly dispersed. The resulting solution was placed in a mold and dried to constant weight at room temperature and pressure to obtain the final product.

[0035] Comparative Example 4: Comparative Example 4 differs from Example 1 only in that the drying method is changed from ambient temperature and pressure to vacuum drying. The vacuum drying temperature is 80°C and the time is 6 hours. The rest is the same as Example 1.

[0036] Comparative Example 5: Comparative Example 5 differs from Example 1 only in that the drying method is changed from room temperature and pressure to freeze drying, with a freeze drying temperature of -40°C and a time of 24 hours. Otherwise, it is the same as Example 1.

[0037] Comparative Example 6: Comparative Example 6 differs from Example 1 only in that the solvent tert-butanol is replaced with anhydrous ethanol; otherwise, they are the same as Example 1.

[0038] Test case 1. Infrared spectroscopy was performed on the ethyl cellulose-based phase change organic gel obtained in Example 1. The results are shown in the figure. Figure 1 .

[0039] Depend on Figure 1 It can be seen that, for polyethylene glycol, 3417 cm -1 The absorption peak at this location is attributed to -OH, while in the spectrum of ethyl cellulose-based phase change organogels, the -OH absorption peak shifts to 3428 cm⁻¹. -1 This indicates that hydrogen bonds have formed between polyethylene glycol, ethyl cellulose, hydrophobic silica, and cellulose nanocrystals.

[0040] 2. Differential scanning calorimetry (DSC) was performed on the materials obtained in Example 1 and Comparative Examples 1 to 6. The results are shown in Table 1.

[0041] Table 1 DSC results for different materials

[0042] As shown in Table 1, compared to the phase change organic gels formed by a single component, the multi-component phase change organic gel material (polyethylene glycol / ethyl cellulose / hydrophobic silica / cellulose nanocrystals) exhibits a phase change enthalpy as high as 130.5 J / g, demonstrating better phase change heat storage characteristics. The phase change enthalpies of the other single-component / two-component phase change organic gel materials are all lower than those of the multi-component materials (Comparative Examples 1-3). This is mainly because the cross-linked network formed by the multi-component materials is denser than that of the single / two-component materials, allowing for the binding of more polyethylene glycol phase change material. Furthermore, the phase change enthalpy of the material obtained by replacing the solvent with ethanol is lower than that obtained with tert-butanol (Example 1 and Comparative Example 6). This is primarily because the surface tension of tert-butanol is lower than that of ethanol. During the drying process, tert-butanol is less likely to destroy the formed cross-linked network structure when it evaporates, while ethanol easily does. Therefore, the phase change enthalpy of the organic phase change gel material in ethanol solvent is lower than that in the tert-butanol system. Furthermore, the phase transition enthalpy of materials dried at room temperature and pressure is higher than that of materials dried under vacuum. This is mainly because solvent evaporation is slower at room temperature and pressure, making it less likely to damage the formed cross-linked structure. The phase transition enthalpy of materials dried at room temperature and pressure is quite close to that of materials freeze-dried, indicating that drying at room temperature and pressure does not easily damage the formed cross-linked structure, requires less energy and relies on expensive equipment, and is suitable for large-scale industrial production.

[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An ethyl cellulose-based phase change organic gel, characterized in that, It includes the following components by weight percentage: 60-70 wt% polyethylene glycol, 15-20 wt% ethyl cellulose, 12-15 wt% hydrophobic fumed silica, and 3-5 wt% strength enhancer.

2. The ethyl cellulose-based phase change organic gel according to claim 1, characterized in that, The composition includes the following components by weight percentage: 70 wt% polyethylene glycol, 15 wt% ethyl cellulose, 12 wt% hydrophobic fumed silica, and 3 wt% strength enhancer.

3. The ethyl cellulose-based phase change organic gel according to claim 1 or 2, characterized in that, The strength enhancer is cellulose nanocrystals and / or carboxylated cellulose nanocrystals.

4. The ethyl cellulose-based phase change organic gel according to claim 1 or 2, characterized in that, The polyethylene glycol is at least one of polyethylene glycol 1000, polyethylene glycol 2000 and polyethylene glycol 3400.

5. The method for preparing the ethyl cellulose-based phase change organic gel according to any one of claims 1 to 4, characterized in that, Ethyl cellulose was dissolved in a solvent, and hydrophobic fumed silica and a strength enhancer were added. The mixture was stirred until it was evenly dispersed, and then polyethylene glycol was added. The mixture was stirred until it was evenly dispersed, and finally the resulting solution was dried to constant weight at room temperature and pressure.

6. The preparation method according to claim 5, characterized in that, Ethyl cellulose was dissolved in a solvent, hydrophobic fumed silica was added, and the mixture was stirred until it was evenly dispersed. Then, a strength enhancer was added and stirred until it was evenly dispersed. Polyethylene glycol was added and stirred until it was evenly dispersed. The resulting solution was then placed in a mold and dried to constant weight at room temperature and pressure to obtain the final product.

7. The preparation method according to claim 5 or 6, characterized in that, The solvent is tert-butanol.

8. The application of the ethyl cellulose-based phase change organic gel according to any one of claims 1 to 4 in oil adsorption.

9. The use of the ethyl cellulose-based phase change organic gel according to any one of claims 1 to 4 in the preparation of thermal management phase change materials.